2014
DOI: 10.1177/1076029613520488
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Correlation Between Coronary Artery Ectasia and Neutrophil–Lymphocyte Ratio?

Abstract: We aimed to investigate the association between the neutrophil-lymphocyte ratio (NLR) and coronary artery ectasia (CAE). The study included 198 patients who had undergone coronary angiography for suspected coronary artery disease (CAD). The patients were divided into the following 4 groups: group 1, 44 patients with normal coronary arteries; group 2, 61 patients with CAD; group 3, 40 patients with isolated CAE; and group 4, 53 patients with CAE coexisting with CAD. Neutrophil-lymphocyte ratio was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…As previously mentioned, CAE is an inflammatory process,12)13)14)17) and there is a study that proves it to be so. In a study conducted by Yalcin et al,17) there is a significant statistical result between NLR and CAE, and it was concluded that we can also evaluate these results by using Markis classification 18).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As previously mentioned, CAE is an inflammatory process,12)13)14)17) and there is a study that proves it to be so. In a study conducted by Yalcin et al,17) there is a significant statistical result between NLR and CAE, and it was concluded that we can also evaluate these results by using Markis classification 18).…”
Section: Discussionmentioning
confidence: 93%
“…In a study conducted by Yalcin et al,17) there is a significant statistical result between NLR and CAE, and it was concluded that we can also evaluate these results by using Markis classification 18). Also, in another study, redcell-distribution (RDW) was used as an easily-accessible marker: Isik et al19) and Guo et al20) proposed some possible mechanistic explanations of the relationship between RDW and CAE, and found that elevation in the RDW values is associated with both the presence and severity of the CAE.…”
Section: Discussionmentioning
confidence: 97%
“…16 In addition, CRP, an easier, cheaper and more accessible infl ammatory biomarker, was found to be higher in CAE patients than normal controls. 17,18 Adhesion molecules are known to promote infl ammation by facilitating the activity of immune system cells. Plasma levels of these molecules, such as intercellular adhesion molecule-1 (ICAM-1), vascular adhesion molecule-1 (VCAM-1) and E-selectin, were found to be significantly higher in CAE patients.…”
Section: Discussionmentioning
confidence: 99%
“…18,20,21 Atherosclerosis is linked to aneurysm formation through a process of inflammation, extending into the tunica media, which eventually causes degeneration of the cystic media. 22 Prior studies have demonstrated that the elevation of inflammatory markers such as plasma soluble adhesion molecules, leukocytes, adiponectin, lipoprotein-associated phospholipase-A2, C-reactive protein, plasminogen activator inhibitor-1, IL-1, TNF-alfa and IL-10 are significantly in-Acta Cardiol Sin 2019;35: [20][21][22][23][24][25][26] Blood Viscosity and Coronary Artery Ectasia creased in patients with CAE. [4][5][6][7][8][9][10][11][12] In addition, NLR ratio, as a marker of inflammation, has been associated with atherosclerosis and CAE.…”
Section: Discussionmentioning
confidence: 99%